Positron emission tomography and positron emission tomography-computerized tomography in pediatric patients - Patel Chetan; Kumar Rakesh (Wolters Kluwer Medknow Publications, 2007)
Positron emission tomography (PET) is a functional diagnostic modality, which is routinely used in oncology for diagnosis, staging, monitoring the response to therapy, and restaging of various tumors. PET used in conjunction with computerized tomography (CT) (PET-CT) is more useful as it provides anatomical details and the abnormal uptake on PET can be localized with highest accuracy. Much work has been done regarding PET/PET-CT in the adults but there is paucity in the same in pediatric group. A child must receive special attention when embarking on what is uncertain and often a frightening procedure. While performing PET in pediatric patients, emphasis is given to patient consent, intravenous access, bladder catheterization, and sedation. Based on existing literature and our own experience, we understand that PET-CT can play a very important role in initial staging, restaging, and evaluation of treatment response in lymphoma, neuroendocrine tumors and bone, and soft tissues sarcoma.